Features of Phacoemulsification in Macular Pathology. Part 1. Diagnostic Aspects - Yusef Naim Yusef; M. V. Vorobyeva; E. E. Kazaryan; N. Yu. Shkolyarenko (Oftalʹmologiâ)
Cataract is the most common cause of blindness worldwide. The standard treatment for cataracts is phacoemulsification with implantation of an intraocular lens (IOL). Removing cataracts can significantly improve vision and the quality of life associated with vision. The review considers the necessary biometric studies before phacoemulsification of patients with macular pathology, the long-term effects of phacoemulsification in patients with various macular pathologies, the features of implantation of mono- and multifocal IOLs in such patients, as well as possible complications after phacoemulsification in patients with macular pathology. The importance of examination of the macula before phacoemulsification of cataract has been shown. A review of changes in different eye’s parts after phacoemulsification in patients with various pathologies: with the progression of myotic traction, with combined cataract and glaucoma, in patients with diabetes, with an epiretinal membrane, and the features of implantation of multifocal lenses and IOLs with UV protection are considered. Not only the postoperative condition is assessed, but also the changes between the preoperative and postoperative conditions. In addition, the review demonstrates the dynamic healing processes and changes in macular parameters (after different times — from several days to several years) in order to obtain a rational analysis result.